Domain 5 of cleaved high molecular weight kininogen inhibits endothelial cell migration through Akt - Katkade, Vaibhav; Soyombo, Abigail A.; Isordia-Salas, Irma; Bradford, Harlan N.; Gaughan, John P.; Colman, Robert W.; Panetti, Tracee S. (Thrombosis and Haemostasis, 2005)
Domain 5 (D5) of cleaved high molecular weight kininogen (HKa) inhibits angiogenesis in vivo and endothelial cell migration in vitro, but the cell signaling pathways involved in HKa and D5 inhibition of endothelial cell migration are incompletely delineated. This study examines the mechanism of HKa and D5 inhibition of two potent stimulators of endothelial cell migration, sphingosine 1-phosphate (S1P) and vascular endothelial growth factor (VEGF), that act through the PI3-kinase-Akt signaling pathway. HKa and D5 inhibit bovine pulmonary artery endothelial cell (BPAE) or human umbilical vein endothelial cell chemotaxis in the modified-Boyden chamber in response to VEGF or S1P. The inhibition of migration by HKa is reversed by antibodies to urokinase-type plasminogen activator receptor. Both HKa and D5 decrease the speed of BPAE cell migration and alter the morphology in live, time-lapse microscopy after stimulation with S1P or VEGF. HKa and D5 reduce the localization of paxillin to the focal adhesions after S1P and VEGF stimulation. To better understand the intracellular signaling pathways, we examined the effect of HKa on the phosphorylation of Akt and its downstream effector, GSK-3α.HKa and D5 inhibit phosphorylation of Akt and GSK-3α after stimulation withVEGF and S1P. Inhibitors of Akt and PI3-kinase, the upstream activator of Akt, block endothelial cell migration and disrupt paxillin localization to the focal adhesions after stimulation with VEGF and S1P. Therefore we suggest that HKa through its D5 domain alters PI3-kinase- Akt signaling to inhibit endothelial cell migration through alterations in the focal adhesions.
Keywords: Angiogenesis; high molecular weight kininogen; sphingosine 1-phosphate; vascular endothelial growth factor; migration